The Influence of Legal Awareness on Public Compliance with Laws and Regulations - Dadi Waluyo; Sumardi (AKADEMI TEKNIK ADI KARYA, 2026)
Legal awareness has become a fundamental determinant of public compliance with laws and regulations, particularly in the context of increasingly complex governance systems and the demand for effective law enforcement. Despite continuous legal reforms, variations in public compliance remain evident due to differences in individuals' understanding, attitudes, and perceptions of legal norms. This study aims to examine the influence of legal awareness on public compliance with laws and regulations. The research employed a quantitative explanatory design using a survey approach. Data were collected from members of the public through structured questionnaires using proportionate random sampling. Legal awareness was measured through four dimensions, namely legal knowledge, legal understanding, legal attitude, and legal behavior, while public compliance was assessed based on individuals' adherence to statutory obligations and regulatory requirements. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the reliability and validity of the measurement model and to test the proposed structural relationships. The findings indicate that legal awareness has a positive and statistically significant effect on public compliance with laws and regulations. Individuals with higher levels of legal knowledge and stronger legal attitudes demonstrate greater willingness to obey legal norms and fulfill their civic obligations. Furthermore, legal awareness contributes to the internalization of legal values, strengthens trust in legal institutions, and promotes voluntary compliance rather than compliance driven solely by fear of sanctions. These findings highlight the strategic importance of legal education and awareness programs in fostering a sustainable culture of lawfulness. The study contributes to the literature on legal compliance by providing empirical evidence that strengthening legal awareness is an essential mechanism for improving public adherence to legal regulations and supporting effective governance.